Readthrough of stop codons under limiting ABCE1 concentration involves frameshifting and inhibits nonsense-mediated mRNA decay. Issue 18 (17th September 2020) - Annibaldis, Giuditta; Domanski, Michal; Dreos, René; Contu, Lara; Carl, Sarah; Kläy, Nina; Mühlemann, Oliver
Abstract: To gain insight into the mechanistic link between translation termination and nonsense-mediated mRNA decay (NMD), we depleted the ribosome recycling factor ABCE1 in human cells, resulting in an upregulation of NMD-sensitive mRNAs. Suppression of NMD on these mRNAs occurs prior to their SMG6-mediated endonucleolytic cleavage. ABCE1 depletion caused ribosome stalling at termination codons (TCs) and increased ribosome occupancy in 3′ UTRs, implying enhanced TC readthrough. ABCE1 knockdown indeed increased the rate of readthrough and continuation of translation in different reading frames, providing a possible explanation for the observed NMD inhibition, since enhanced readthrough displaces NMD activating proteins from the 3′ UTR. Our results indicate that stalling at TCs triggers ribosome collisions and activates ribosome quality control. Collectively, we show that improper translation termination can lead to readthrough of the TC, presumably due to ribosome collisions pushing the stalled ribosomes into the 3′ UTR, where it can resume translation in-frame as well as out-of-frame.